2022
DOI: 10.1002/smll.202200319
|View full text |Cite
|
Sign up to set email alerts
|

Automated and Dynamic Control of Chemical Content in Droplets for Scalable Screens of Small Animals

Abstract: the limited ability to change the environment and 3D animal motion make it difficult to assess dynamic phenotypes other than rough motion analysis. In contrast, microfluidics, with relevant length scales down to the animal's size, offers improved means to handle small animals and control their environment. [10][11][12][13][14] Animals can be confined in 2D or even immobilized, and liquids can be exchanged rapidly. These approaches enable advanced functional assays such as monitoring brain activity [15,16] or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Copyright 2022 Wiley (). (B) Liquid exchanger to exchange the chemical environment of one droplet with another without losing the encapsulated object (ref ). Adapted with permission from Automated and Dynamic Control of Chemical Content in Droplets for Scalable Screens of Small Animals, Aubry, G.; Milisavljevic, M.; Lu, H. Small , Vol.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2022 Wiley (). (B) Liquid exchanger to exchange the chemical environment of one droplet with another without losing the encapsulated object (ref ). Adapted with permission from Automated and Dynamic Control of Chemical Content in Droplets for Scalable Screens of Small Animals, Aubry, G.; Milisavljevic, M.; Lu, H. Small , Vol.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
“…Up to 88% of the original solution in the droplet could be exchanged with the new solution while keeping cell loss to less than 5%. Aubry et al developed a liquid exchanger passive system to dynamically control the chemical environment of small animals encapsulated in droplets (Figure B) . By careful use of interfacial forces, the liquid exchanger unit allows for adding and removing chemicals from a droplet and, therefore, generating chemical gradients inaccessible in previous multiphase systems.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For multicellular organisms, some ecotoxicity studies were reported, for example, with: rotifers (Brachionus calyciflorus) (Cartlidge and Wlodkowic, 2018), Crustacea (Artemia sp.) (Huang et al, 2015), Allorchestes copressa (Cartlidge et al, 2017) and Daphnia magna (Huang et al, 2017;Tabatabaei Anaraki et al, 2018), nematode (Caenorhabditis elegans) Zhang et al, 2021;Aubry et al, 2022) and fish (Danio rerio) models (Yang et al, 2016;Khalili and Rezai, 2019).…”
Section: Innovative Approaches To Assessing Nms Toxicity Using Daphni...mentioning
confidence: 99%
“…As one of the best-investigated small animal models, Caenorhabditis elegans ( C. elegans ) has been extensively employed in large-scale genetic and pharmacological screenings, benefiting from its various experimental advantages including tiny size, body transparency, short life span, well-characterized genetics, and low-cost maintenance. Moreover, numerous C. elegans disease models have also been well developed to recapitulate distinctive phenotypes of human diseases, such as pathogen infections, which has paved the way for deep profiling candidate therapeutics at a whole organism level. However, it is still challenging to screen C. elegans for behaviors that unfold over a long period and evaluate quickly and accurately in real time via traditional manually assisted screening techniques. Even though various microfluidic systems have been developed to screen C. elegans , the complex external systems have highly restricted their applicability. Particularly, almost all the proposed platforms are based on microscopic imaging with a high-speed camera, which further limited their employment due to the high cost and low throughput in long-term evaluations. Therefore, a practical, cost-effective and high-throughput system for in vivo screening of C. elegans is still clearly needed in the fields of biology and pharmacology.…”
mentioning
confidence: 99%